2016
DOI: 10.1186/s12995-016-0138-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of moulded hearing protectors by child care workers - an interventional pilot study

Abstract: BackgroundEmployees of a multi-site institution for children and adolescents started to wear moulded hearing protectors (MHPs) during working hours, as they were suffering from a high level of noise exposure. It was agreed with the institutional physician and the German Institution for Statutory Accident Insurance and Prevention in the Health and Welfare Services (BGW) that this presented an opportunity to perform a scientific study to investigate potential beneficial effects on risk of burnout and subjective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…This is likely partly explained by perceived detrimental effects of hearing protection devices use on speech perception. Preschool personnel may also find it inappropriate to wear HPDs in the presence of parents and may consider that wearing HPDs reduces their ability to fulfill their teaching duties ( Koch et al 2016 ). According to the Swedish Work Environment Authorities regulation on noise at work, the use of HPDs is a hearing prevention measure taken when other noise abatement measures have failed, such as replacing or isolating noisy machines.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely partly explained by perceived detrimental effects of hearing protection devices use on speech perception. Preschool personnel may also find it inappropriate to wear HPDs in the presence of parents and may consider that wearing HPDs reduces their ability to fulfill their teaching duties ( Koch et al 2016 ). According to the Swedish Work Environment Authorities regulation on noise at work, the use of HPDs is a hearing prevention measure taken when other noise abatement measures have failed, such as replacing or isolating noisy machines.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of a spill-over of psychosocial factors, but also biomechanical stress from employees’ private lives, also could not be excluded since these factors were not recorded as part of the study. Furthermore, part of the sample population (31%) took part in a parallel occupational preventive programme for the reduction of subjective noise exposure [ 28 ]. Although the study did not appear to have a statistically significant intervention effect, there were indications that the intervention group showed some benefits in terms of burnout as compared with the reference group.…”
Section: Discussionmentioning
confidence: 99%
“…After twelve months (follow up), all study participants once again received a copy of the same pseudonymised questionnaire they had completed a year before. A subgroup of participants ( n = 33) took part in a parallel intervention programme looking at the effects of noise in the workplace [ 28 ]. In that study, the focus was on the question of whether the use of personal hearing protection over the observational period of one year could reduce the subjective noise exposure and the risk of burnout among childcare workers.…”
Section: Methodsmentioning
confidence: 99%
“…Noise is a common workplace problem that can negatively affect health, well-being and performance hearing protection devices (HPDs) in childcare work-88 ers in an institution for children and adolescents [15].…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that the noise-reduction strategies resulted in a more quiet work environment, benefiting both staff and patients. Yet another intervention study investigated the use of hearing protection devices (HPDs) in childcare workers in an institution for children and adolescents [ 15 ]. A little more than half of the participants reported that they were still capable of fulfilling their teaching duties while wearing the HPDs.…”
Section: Introductionmentioning
confidence: 99%